Mini Review: Proses Ekstraksi dan Karakteristik Fisiko-Kimia Virgin Coconut Oil - Rozali, Zalniati Fonna (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Virgin coconut oil (VCO) is one of the processed products from old coconut flesh, which is increasingly popular as a food supplement, nutraceutical, lotion, and solvent for aromatherapy products. The high demand for VCO is related to the quality of the fatty acids that make up VCO. This is influenced by the extraction process carried out at low temperatures so as to maintain the composition and quality of fatty acids in VCO, which can be observed from the characteristics of the resulting VCO. This article presents a brief review of several literatures related to several methods for extracting VCO and the characteristics of VCO that meet standards obtained from various references. The VCO extraction methods presented are the enzymatic method, fermentation method, fishing method, stirring method, controlled heating method, and acidification method. Each of these methods has advantages and disadvantages in the characteristics of the resulting VCO.